2021
DOI: 10.1108/cr-02-2021-0026
|View full text |Cite
|
Sign up to set email alerts
|

Smart economic development patterns in Europe: interaction with competitiveness

Abstract: Purpose This paper aims to investigate the smart economic development (SED) patterns in Europe in relation to competitiveness. Motivational focus corresponds to global events: the fourth industrial revolution, transition to a low-carbon economy, economic shocks (such as the 2008 financial crisis, Brexit or the coronavirus pandemic), which requires rethinking development policies, targeting competitiveness increase and reducing imbalances in economic development. Design/methodology/approach The analysis inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Research on EU countries in this respect has shown that smart economic development facilitates the improvement of the productivity of land, labor and capital, thus driving competitiveness. The key determinants of competitiveness in this approach are legal environment, social responsibility, competence and knowledge building, and social security of employees [Bruneckiene, Rapsikevicius, Lukauskas, Zykiene, Jucevicius, 2021]. Similar analyses were carried out for Central and Eastern European countries [Dagiliene, Bruneckiene, Jucevičius, Lukauskas, 2020].…”
Section: Conclusion From the Review Of The Latest Research Resultsmentioning
confidence: 86%
“…Research on EU countries in this respect has shown that smart economic development facilitates the improvement of the productivity of land, labor and capital, thus driving competitiveness. The key determinants of competitiveness in this approach are legal environment, social responsibility, competence and knowledge building, and social security of employees [Bruneckiene, Rapsikevicius, Lukauskas, Zykiene, Jucevicius, 2021]. Similar analyses were carried out for Central and Eastern European countries [Dagiliene, Bruneckiene, Jucevičius, Lukauskas, 2020].…”
Section: Conclusion From the Review Of The Latest Research Resultsmentioning
confidence: 86%
“…Badania przeprowadzone pod tym kątem wśród krajów Unii Europejskiej (UE) pokazały, że inteligentny rozwój (smart economic development) umożliwia poprawę produktywności ziemi, pracy i kapitału, wpływając tym samym na konkurencyjność. Kluczowymi determinantami konkurencyjności są w tym przypadku: porządek prawny, odpowiedzialność społeczna, budowanie kompetencji i tworzenie wiedzy oraz zabezpieczenie socjalne zatrudnionych [Bruneckiene, Rapsikevicius, Lukauskas, Zykiene, Jucevicius, 2021]. Podobne analizy przeprowadzono dla krajów Europy Środkowo-Wschodniej [Dagiliene, Bruneckiene, Jucevičius, Lukauskas, 2020].…”
Section: Wnioski Z Przeglądu Wyników Najnowszych Badańunclassified
“…Scientists operating in the fi eld of economics assert that competitiveness is one of the substantial elements infl uencing the level of a country's economic development (Bruneckienė et al, 2021;Muradov et al, 2019;Mynkin, 2017). Moreover, competitiveness diminishes the size of the shadow economy (Poufi nas et al, 2021), which, in turn, could infl uence overall economic growth.…”
Section: Introductionmentioning
confidence: 99%